Information technology, governance and insurance in sub-Saharan Africa - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2019)
Purpose - This study investigates the role of ICT in modulating the effect of governance on insurance penetration in 42 sub-Saharan African countries using data for the period 2004- 2014. Design/methodology/approach -Two insurance indicators are used in the analysis, namely: life insurance and non-life insurance. The three ICT modulating dynamics employed include: mobile phone penetration, internet penetration and fixed broadband subscriptions. Six governance channels are also considered, namely: political stability, "voice & accountability", regulation quality, government effectiveness, the rule of law and corruption-control. The empirical evidence is based on generalized method of moments. Findings -The following main findings are established. First, mobile phone penetration does not significantly modulate governance channels to positively affect life insurance while it effectively complements "voice & accountability" to induce a positive net effect on non-life insurance. Second, internet penetration complements: (i) governance dynamics of political stability, government effectiveness and rule of law to induce positive net effects on life insurance: and (ii) corruption-control for an overall positive effect on non-life insurance. Third, the relevance of fixed broadband subscriptions in promoting life insurance is apparent via governance channels of regulation quality, government effectiveness and the rule of law while fixed broadband subscriptions do not induce significant overall net effects on non-life insurance though the conditional effects are overwhelmingly significant. Orginality/value - To the best our knowledge, studies on the relevance of ICT in promoting insurance consumption through governance channels are sparse, especially for a region such as sub-Saharan Africa where insurance penetration is low compared to other regions of the world.
Keywords: G20; I28; I30; L96; O55; 330; Africa; ICT; Governance; Insurance